THE LEGITIMACY OF THE ESTABLISHMENT OF THE KURDISH STATE - A SHARIA-BASED OBJECTIVE STUDY - MMuhammad Ibrahimuhammad, Masoud; Ibrahim, Ayad (Humanities Journal of University of Zakho, 2025)
This study aims to explore the legitimacy of the establishment of a Kurdish state from the perspective of Islamic law, within an integrated methodological framework that combines text-based legal foundations and the objectives of the tolerant Islamic law. The study is based on the firm premise that Islamic law is characterized by its comprehensiveness across all aspects of human life, including belief, worship, ethics, and transactions, and that it is indivisible and indivisible. The study addresses the issue from multiple perspectives: doctrinal, ethical, and political-legal. It seeks to ground the project of establishing a Kurdish state in definitive and established texts from the Holy Quran and the Prophetic Sunnah, which are the two primary sources of Islamic legislation. The study also highlights the pivotal role of valid ijtihad evidence, such as custom, public interest (maslahah) that serves all Muslims, and the objectives of Islamic law, in constructing a comprehensive legal conception of the legitimacy of the establishment of a Kurdish state. The study also addresses the most prominent doubts raised about this proposal, working to refute them and provide responses in a sound and rigorous scientific manner. The study concludes that the demand for a Kurdish state is not merely a political aspiration, but rather represents—in light of precise Sharia and objective criteria—a pressing Sharia necessity in light of the current political and social reality. This affirmation comes in fulfillment of the major and supreme objectives of Sharia, the original and essential ones, foremost among which are the establishment of comprehensive justice, the preservation of the five necessities (religion, life, reason, lineage, and wealth), and the realization of the principle of complete equality among Muslims in rights and duties.